The Root Canal Biofilm - Chávez de Paz, Luis E.; Sedgley, Christine M.; Kishen, Anil.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book presents the current state of research on the basic scientific aspects of root canal biofilm biology within a clinically applicable context. Root canal biofilms are complex polymicrobial structures adhering to the root canal surface that are formed by microorganisms invading the pulpal space of teeth, and are associated with persistent root canal infections. Concerted efforts to study root canal biofilms have been made in the past decade, resulting in the publication of observational and experimental studies that detail the morphology and biology of these structures in infected root canals. In addition to confirming that bacteria in root canals do not exist in free-floating planktonic states as previously assumed, this new information on root canal biofilm infections has provided an opportunity to re-evaluate conventional clinical protocols and improve endodontic therapeutic measures. .
Part I: General Biological Aspects -- Ecology and Physiology of Root Canal Microbial Biofilm Communities -- Molecular Principles of Adhesion and Biofilm Formation -- Antimicrobial Resistance in Biofilm Communities -- Part II: Observational and Experimental Evidence -- The Use of Scanning Electron Microscopy (SEM) in Visualizing the Root Canal Biofilm -- Bacterial Biofilms and Endodontic Disease: Histo-Bacteriological and Molecular Exploration -- Laboratory Models of Biofilms: Development and Assessment -- Root Canal Anatomy: Implications in Biofilm Disinfection -- Part III: Outcome and Strategies of Treatment -- Biofilm-Associated Infections in Root Canals Treatment and Outcomes -- Root Canal Irrigation -- Inter-Appointment Medication with Calcium Hydroxide in Routine Cases of Root Canal Therapy -- Chapter 11. Advanced Therapeutic Options to Disinfect Root Canals.
Keywords: Microbiology; Dentistry; Infectious diseases; Microscopy; Microbiology; Dentistry; Infectious Diseases; Biological Microscopy